2003
DOI: 10.1021/ja037290e
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Syntheses of Aeruginosin 298-A and Its Analogues Using a Catalytic Asymmetric Phase-Transfer Reaction and Epoxidation

Abstract: We developed a versatile synthetic process for aeruginosin 298-A as well as several attractive analogues, in which all stereocenters were controlled by a catalytic asymmetric phase-transfer reaction and epoxidation. Furthermore, drastic counteranion effects in phase-transfer catalysis were observed for the first time, making it possible to three-dimensionally fine-tune the catalyst (ketal part, aromatic part, and counteranion).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 11 publications
1
60
0
5
Order By: Relevance
“…Based on the structure of aeruginosin 102-A (1b), we also synthesized the D-Tyr analog D-3b (88%, 92% ee) and the D-Phe(4-F) analog D-3c (93%, 94% ee). During the scaling-up of the reaction, we found that after quenching the reaction with water and ether, catalyst 2 was deposited as a white solid and easily recoverable in Ϸ90% yield just by simple decantation (15). This finding suggests that catalyst 2 is extremely stable even under strongly basic conditions in contrast to commonly used Cinchona alkaloid derived catalysts (24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Based on the structure of aeruginosin 102-A (1b), we also synthesized the D-Tyr analog D-3b (88%, 92% ee) and the D-Phe(4-F) analog D-3c (93%, 94% ee). During the scaling-up of the reaction, we found that after quenching the reaction with water and ether, catalyst 2 was deposited as a white solid and easily recoverable in Ϸ90% yield just by simple decantation (15). This finding suggests that catalyst 2 is extremely stable even under strongly basic conditions in contrast to commonly used Cinchona alkaloid derived catalysts (24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 88%
“…When using 10 mol % of (S,S)-2a, phase-transfer alkylation of 4 proceeded smoothly to afford a variety of ␣-amino acids (14,15). For the synthesis of 1a (D-Leu portion), methallyl bromide was used as an electrophile to afford D-3a [93%, 91% enantiomeric excess (ee)].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations